KEKUATAN HUKUM HIBAH TANAH SECARA LISAN MENURUT FIQH DAN HUKUM PERDATA TERHADAP OBJEK TANAH SDN 212 KELURAHAN KENALI ASAM BAWAH KECAMATAN KOTA BARU KOTA JAMBI - M. Khodadan Ryan Keano; Ruslan Abdul Ghani; Rahmi Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
A grant is an agreement in which a person freely and irrevocably gives an item to another party during his lifetime. The practice of oral land grants is still common in the community, especially in kinship circles based on mutual trust. However, when the object of the grant becomes a public asset such as the land of a Public Elementary School (SDN), legal issues arise regarding the evidence and legality of the transfer of rights. This research analyzes the legal force of oral grants from the perspective of Islamic fiqh and civil law, with a case study of SDN 212 land in Kenali Asam Bawah Village, Jambi City. The method used is a normative juridical approach through analysis of Islamic law literature, civil law, and contemporary fiqh expert opinions. In fiqh, oral grants are valid if accompanied by ijab-qabul and the transfer of real rights (qabdh), while positive law requires written evidence and official records. The research found that land grants to the government were made orally based on the provisions in the Compilation of Islamic Law (KHI), but the absence of formal documentation and the absence of an agreement between the Jambi City Government and the Batanghari Regency Government led to a legal dispute. The Jambi District Court ruled in favor of Hermanto as the legal owner based on the 1986 certificate. The findings emphasize the importance of strong evidence and legal recording in grant practices to protect ownership rights and prevent future conflicts.